Aliran-aliran Filsafat Pendidika Schools of Thought in Islamic Philosophy of Education and Their Implications for Contemporary Education - Fatma Azzahra; M Faza Zahiduzaka; Mohammad Rohman Rifai; Ahmad Sulthon (The Future of Education Journal, 2026)
This article examines the streams of Islamic educational philosophy and their relevance to contemporary Islamic education. The study is motivated by the tendency of Islamic education practices to focus on administrative curriculum and instructional routines without adequate philosophical awareness. Using library research with descriptive-analytical content analysis, this article reviews classical and contemporary sources on Islamic educational philosophy, especially the typology of religious-conservative, religious-rational, pragmatic-instrumental, and integrative-tawhidic streams. The findings show that each stream contributes a distinct orientation: moral-spiritual formation, rational and scientific development, social usefulness and life skills, and the integration of knowledge through tawhid and adab. The article argues that these streams should not be treated as mutually exclusive categories, but as complementary perspectives for reconstructing Islamic education. The proposed synthesis emphasizes the unity of faith, knowledge, character, critical reasoning, and social responsibility. This study contributes a conceptual map, an algorithmic model, and practical implications for curriculum design, teaching methods, teacher roles, and evaluation in Islamic education.